Luqman Hakim Boarding Students Training Rowolaku In Effective Financial Management And Efficient - Siska Yuliana; Shifa Pramuditha; Nok Karima; Ela Agelia; Hendri Hermawan Adinugraha; Gregory Baron (Pengabdian: Jurnal Abdimas, 2023)
Background. This socialization aims to find out how to manage finances more effectively and efficiently to increase the awareness and ability of female students to manage finances which will later be able to motivate and familiarize them with being able to live independently in meeting their daily needs at the Luqman Hakim Islamic boarding school. Purpose. Financial management is the most important element in achieving financial success. Financial problems should not be taken lightly, for this reason, it is necessary to socialize the importance of financial management for students so that finances can be used more effectively and efficiently. Method. This study used a qualitative method based on the results of direct field observations. Results. This assistance socialization resulted in the conclusion that each female student was able to make realistic financial plans, manage expenses, and maintain discipline in following these plans. Conclusion. This also applies to the female students of the Luqman Hakim Rowolaku Islamic boarding school so that financial problems do not become a burden in the process of seeking knowledge so that they focus on learning to accept the knowledge being taught. They are also able to avoid unnecessary expenses and improve their ability to manage money wisely. They can internalize and apply the taught financial management principles, as well as experience positive changes in the management of their finances. This shows that this assistance is effective in helping female students build financial stability and financial independence.